The novel CXCR4 antagonist, PRX177561, reduces tumor cell proliferation and accelerates cancer stem cell differentiation in glioblastoma preclinical models. Issue 6 (June 2017) - Gravina, Giovanni Luca; Mancini, Andrea; Colapietro, Alessandro; Vitale, Flora; Vetuschi, Antonella; Pompili, Simona; Rossi, Giulia; Marampon, Francesco; Richardson, Peter J; Patient, Lee; Patient, Lee; Burbidge, Stephen; et al.
Glioblastoma is the most frequent and the most lethal primary brain tumor among adults. Standard of care is the association of radiotherapy with concomitant or adjuvant temozolomide. However, to date, recurrence is inevitable. The CXCL12/CXCR4 pathway is upregulated in the glioblastoma tumor microenvironment regulating tumor cell proliferation, local invasion, angiogenesis, and the efficacy of radio-chemotherapy. In this study, we evaluated the effects of the novel CXCR4 antagonist, PRX177561, in preclinical models of glioblastoma. CXCR4 expression and PRX177561 effects were assessed on a panel of 12 human glioblastoma cells lines and 5 patient-derived glioblastoma stem cell cultures. Next, the effect of PRX177561 was tested in vivo, using subcutaneous injection of U87MG, U251, and T98G cells as well as orthotopic intrabrain inoculation of luciferase-transfected U87MG cells. Here we found that PRX177561 impairs the proliferation of human glioblastoma cell lines, increases apoptosis, and reduces CXCR4 expression and cell migration in response to stromal cell–derived factor 1alpha in vitro. PRX177561 reduced the expression of stem cell markers and increased that of E-cadherin and glial fibrillary acidic protein in U87MG cells consistent with a reduction in cancer stem cells. In vivo, PRX177561 reduced the weight and increased the time to progression of glioblastoma subcutaneous tumors while increasing disease-free survival and overall survival of mice bearing orthotopic tumors. Our findings suggest that targeting stromal cell–derived factor 1 alpha/CXCR4 axis by PRX177561 might represent a novel therapeutic approach against glioblastoma and support further investigation of this compound in more complex preclinical settings in order to determine its therapeutic potential.